2020
DOI: 10.1097/htr.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Activity Level During Acute Concussion May Predict Symptom Recovery Within an Active Duty Military Population

Abstract: Objective: To evaluate the impact on symptom resolution of activity acutely following a concussion and the role of acute-phase symptoms on this relationship among active duty service members (SMs). Setting: Three military installations. Participants: Sixty-two SMs aged 18 to 44 years who sustained a concussion within 72 hours of enrollment. Design: Longitudinal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 38 publications
5
22
1
Order By: Relevance
“…Optimal patterns of activity during the course of concussion recovery may depend on the severity of symptoms experienced in the acute stage. In a recent study by our group, greater activity level at acute stages of concussion was associated with higher levels of symptoms over time, but only among those with high levels of acute symptoms (9). In the current study, we build upon our previous findings by evaluating the contribution of activities at later stages of concussion rehabilitation post-concussion.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Optimal patterns of activity during the course of concussion recovery may depend on the severity of symptoms experienced in the acute stage. In a recent study by our group, greater activity level at acute stages of concussion was associated with higher levels of symptoms over time, but only among those with high levels of acute symptoms (9). In the current study, we build upon our previous findings by evaluating the contribution of activities at later stages of concussion rehabilitation post-concussion.…”
Section: Introductionmentioning
confidence: 90%
“…A growing body of evidence has shown the importance of monitoring and regulating activity level in the first hours to days following a concussion (28); however, little attention has been given to the contribution of post-acute (i.e., ≥1 month[s]) activity level on symptom recovery in the weeks and months that follow. Furthermore, most of these studies have focused on sports-related concussion (25, 7, 8), while only a limited number provide information about active duty military personnel (9), who may have a greater risk for concussion, and among whom the consequences of persistent impairments impact military force readiness. Research has also been sparse in the evaluation of symptom recovery against activity by specific categories (e.g., cognitive, physical, vestibular/balance).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the negative effects of excessive activity were most prominent for vestibular symptoms, such as dizziness or loss of balance. 26 Results also suggested that patients who did not believe in the importance of rest after concussion experienced slower resolution of symptoms. 32 However, providers who over-emphasize rest-and those who fail to track their concussed patients beyond the initial phase of injury-may also overlook critical opportunities to optimize recovery, as excessive rest during post-acute stages of concussion has been shown to prolong symptoms.…”
Section: Changes In Neurobehavioral Symptoms and Activity Levels Acromentioning
confidence: 95%
“…25 As shown in Figure 1, concussed SMs in the DVBIC PRA study engaged in relatively low levels of activity (and high levels of rest) immediately after injury, followed by gradual increases in activity over the following 3 to 6 months, with an average increase in total activity of 63% over the full study time frame. 26,27 Physical, vestibular/balance, and military-specific activities increased most rapidly, whereas cognitive and lifestyle activities (i.e., reading, socializing, watching television) increased more slowly (Fig. 2).…”
Section: Changes In Neurobehavioral Symptoms and Activity Levels Acromentioning
confidence: 99%